Sonic hedgehog is expressed in human brain arteriovenous malformations and induces arteriovenous malformations in vivo. Issue 2 (February 2021) - Giarretta, Igor; Sturiale, Carmelo L; Gatto, Ilaria; Pacioni, Simone; Gaetani, Eleonora; Porfidia, Angelo; Puca, Alfredo; Palucci, Ivana; Tondi, Paolo; Olivi, Alessandro; Pallini, Roberto; Pola, Roberto
Abnormalities in arterial versus venous endothelial cell identity and dysregulation of angiogenesis are deemed important in the pathophysiology of brain arteriovenous malformations (AVMs). The Sonic hedgehog (Shh) pathway is crucial for both angiogenesis and arterial versus venous differentiation of endothelial cells, through its dual role on the vascular endothelial growth factor/Notch signaling and the nuclear orphan receptor COUP-TFII. In this study, we show that Shh, Gli1 (the main transcription factor of the Shh pathway), and COUP-TFII (a target of the non-canonical Shh pathway) are aberrantly expressed in human brain AVMs. We also show that implantation of pellets containing Shh in the cornea of Efnb2/LacZ mice induces growth of distinct arteries and veins, interconnected by complex sets of arteriovenous shunts, without an interposed capillary bed, as seen in AVMs. We also demonstrate that injection in the rat brain of a plasmid containing the human Shh gene induces the growth of tangles of tortuous and dilated vessels, in part positive and in part negative for the arterial marker αSMA, with direct connections between αSMA-positive and -negative vessels. In summary, we show that the Shh pathway is active in human brain AVMs and that Shh-induced angiogenesis has characteristics reminiscent of those seen in AVMs in humans.